Justice for everyone : the jurisprudence and legal lives of Brenda Hale - Hunter, Rosemary C.; Rackley, Erika (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
As the first woman to be appointed President of the UK Supreme Court, Brenda Hale was one of the UK's most high profile and influential judges, and she is among the most powerful women leaders of our time. For almost half a century, she pioneered as an educator, reformer, and decision-maker, leaving a distinct mark on the law and the lives of many. In commemoration of her recent retirement from the Supreme Court, this collection celebrates her long and illustrious career. Organised by thematic chapters and featuring original research from leading academics, judges and lawyers, this book offers a comprehensive account of Lady Hale's achievements and enduring impact. The contributors, many of whom were her peers and colleagues, demonstrate how Hale forged her own path within male-dominated institutions, carved a space for herself and others, and, ultimately, endeavoured to promote justice for everyone.
Introduction / Rosemary Hunter and Erika Rackley -- On the bench with Brenda / David Neuberger -- Lady Hale - leading from the front : ensuring equality and inclusivity / Gita Mittal -- Lady Hale : a personal reflection / Susan Glazebrook -- Reflections on Lady Hale as an international judge / Beverley McLachlin -- Women and the law school, 1970s-1980s / Celia Wells, Margot Brazier, Lesley Newton, Alison Raeside, Carol Smart, Erika Szyszczak -- Justice and welfare : Lady Hale and the journal of social welfare and family law (formerly journal of social welfare law) / Mavis Maclean -- Celebrating Hoggett and Pearl, the family, law and society 1983-2009 / Daniel Monk -- Writing women and the law / Susan Atkins -- The law reformer : transforming the way that policy is made at the law commission / Linda Mulcahy and Peter G Harris -- Brenda Hale : supporting and inspiring women judges / Laura Cox -- Assessing Lady Hale's impact on the UK's final appeal courts / Alan Paterson -- The qualities of Lady Hale's legal reasoning / Lord Kerr of Tonaghmore -- On personhood for everyone : Brenda Hale's jurisprudence and her institution-building / Judith Resnik -- Lady Hale and access to justice / Hazel Genn and Chris Moss -- Lady Hale in the South African courts : an illustration of the many roles of foreign case law in South African jurisprudence / Catherine O'Regan -- Leading the way : Baroness Hale and the new family law / John Eekelaar -- Debates on marriage and cohabitation / Rebecca Probert -- Lady Hale and financial remedies on divorce / Alison Diduck -- Women and domestic abuse / Felicity Kaganas -- Public child law / Judith Masson -- 'Hang on, what about the child in this case?' Lady Hale, champion of children's rights / Stephen Gilmore -- Orthodox principles and unconventional outcomes in public law / David Feldman -- Lady Hale : rights, and righting wrongs, in immigration and nationality / Devyani Prabhat -- Baroness Hale : the reality and complexity of welfare law / Richard Drabble QC -- 'A homemaker as well as a judge' : Lady Hale and judicial home making/unmaking/remaking / Helen Carr and Jed Meers -- Gender equality and Article 14 ECHR : Lady Hale's contribution / Sandra Fredman -- Mental health and mental capacity law / Victoria Butler-Cole QC -- Lady Hale : relationality, care and medical law / Jonathan Herring -- Brenda Hale : understanding discrimination and championing equality / Karon Monaghan QC -- Materialising the UK Supreme Court / Jenny Rowe -- Picturing Brenda Hale : from painted portraits to moving pictures / Leslie J Moran -- Lady justice : many sides to a story / Susanne Baer -- Music to Honour Lady Hale.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Hale, Brenda; Judges -- Great Britain -- Biography